Impacts of AUKUS Formation on the Dynamics of ASEAN Member States - khresna, afi; wijayanti, ra afera ratna; khrisnamurti, indra (LIAISON JOURNAL OF BEST, 2025)
The establishment of AUKUS alliance in 2021 has resulted in substantial shifts in the geopolitical and security landscape of the Indo Pacific region, especially for ASEAN member states. This study examines the effects and consequences of AUKUS on ASEAN member states, focusing on its impact on regional security frameworks, geopolitical alignments, and the strategic responses of ASEAN member states. Through qualitative research, the study investigates how AUKUS is affecting the balance of power in the Indo-Pacific and challenging each ASEAN member states role as a central player in regional security discussions. The findings indicate that AUKUS has intensified great-power competition, compelling each ASEAN member states to navigate a complex landscape of strategic partnerships and rivalries. Divergent reactions among member states highlight the fragmentation of ASEAN's unified stance, with some viewing AUKUS as a counterbalance to China's assertiveness and others perceiving it as a destabilizing factor. This research underscores the need for each ASEAN members to adapt its strategies to maintain relevance and unity amid evolving geopolitical landscapes. By addressing the challenges brought by AUKUS, this thesis offers valuable insights into the security and geopolitical complexities ASEAN member states faces in the rapidly changing Indo-Pacific region. Keywords: ASEAN, AUKUS, formation, geopolitical, Indo- Pacific